2016
DOI: 10.1007/s10803-016-2762-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Obesity, Physical Activity, and Sedentary Behaviors Between Adolescents With Autism Spectrum Disorders and Without

Abstract: Body mass index classification, physical activity (PA), and sedentary behaviors were compared in adolescents with autism spectrum disorder (ASD) to typically developing adolescents. Participants included 42,747 adolescents (ASD, n = 915) from the 2011-2012 National Survey of Children's Health. After controlling for covariates, adolescents were more likely to be overweight and obese, and less likely to engage in regular PA versus typically developing adolescents (p's < 0.05). Increased odds for overweight and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
127
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(141 citation statements)
references
References 36 publications
12
127
0
2
Order By: Relevance
“…The elevated obesity prevalence based on nationally representative samples in children with ASD compared with those without the condition has been previously reported by our group 10 and others 9,18,24,25,35 as well as in school-based and clinical samples. 8,[26][27][28]36 Chen et al reported an obesity prevalence of 21.1% among 10-17-year-olds in the 2003 round of NSCH, similar to our estimates, and consistent with a leveling off in prevalence trends over time seen in other nationally representative samples of US children.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The elevated obesity prevalence based on nationally representative samples in children with ASD compared with those without the condition has been previously reported by our group 10 and others 9,18,24,25,35 as well as in school-based and clinical samples. 8,[26][27][28]36 Chen et al reported an obesity prevalence of 21.1% among 10-17-year-olds in the 2003 round of NSCH, similar to our estimates, and consistent with a leveling off in prevalence trends over time seen in other nationally representative samples of US children.…”
Section: Discussionsupporting
confidence: 79%
“…24 Using the same dataset, but a slightly different approach, McCoy et al found obesity prevalence of 22.2% in children with ASD compared with 14.1% in children without ASD. 25 In addition, using NSCH 2011-2012, but including a broader age range of children 6-17 years, Corvey et al reported that the observed elevation in obesity prevalence disappeared after accounting for comorbid disorders and medication use. 18 The prevalence of obesity has also been estimated from clinical samples.…”
mentioning
confidence: 99%
“…Moreover, inadequate levels of physical activity cost the United States an estimated annual $131 billion in health care expenditures (Carlson, Fulton, Pratt, Yang, & Adams, ). Individuals with developmental disabilities, such as autism spectrum disorder (ASD) or intellectual disabilities (ID), are even less likely to meet physical activity guidelines compared to the general population; thus, effective methods for increasing daily steps in these populations are needed (CDC, ; Hsieh, Heller, Bershadsky, & Taub, ; McCoy, Jakicic, & Gibbs, ).…”
mentioning
confidence: 99%
“…The most current evidence indicates that children and adolescents with ASD are not sufficiently active and fall short of meeting the Center for Disease Control's Physical Activity Guidelines (Bandini et al, 2013; Obrusnikova & Cavalier, 2011; Memari et al., 2015; McDonald, Esposito & Ulrich, 2011). Several studies have found that youth with ASD are less physically active than their typically developing (TD) peers (McCoy, Jakicic, & Gibbs, 2016; Pan et al. 2016; Tyler et al, 2014), though this finding has not been consistently observed across all age groups (Bandini et al, 2013; Rosser Sandt & Frey, 2005).…”
mentioning
confidence: 99%